«A ratos perdidos (1984-2015)», los diarios de Chirbes en cuadernos nuevos datos para el estudio de su obra - Llamas Martínez, Jacobo (2021)
The texts written by Chirbes in notebooks between 1984 and 2015 and compiled under the title A ratos perdidos contain interesting literary, political and artistic judgments and interpretations of his own work that allow for greater understanding of his life and literary output. This article details several aspects related to his habits and preferences as a reader and writer that could pave the way for future research, given the relevance and scope of the intertextual, narratological and genre-re - lated questions raised.
Los textos escritos por Chirbes en cuadernos entre 1984 y 2015, compilados con el título de A ratos perdidos, contienen juicios e interpretaciones literarias, políticas, artísticas y de su propia obra de interés para ahondar en el conocimiento de su vida y producción. En este trabajo se detallan varios ligados a sus hábitos y preferencias como lector y escritor que pueden propiciar investigaciones futuras por la vigencia y alcance de las cuestiones intertextuales, genéricas y narratológicas planteadas.
Keywords: Chirbes, Rafael, -- 1949-2015; Crítica textual